The Essential Role of Circulating Thyroglobulin in Maintaining Dominance of Natural Regulatory T Cell Function to Prevent Autoimmune Thyroiditis - Kong, Y. M.; Brown, N. K.; Morris, G. P.; Flynn, J. C. (Hormone and Metabolic Research, 2015)
Several key findings from the late 1960s to mid-1970s regarding thyroid hormone metabolism and circulating thyroglobulin composition converged with studies pertaining to the role of T lymphocytes in autoimmune thyroiditis. These studies cemented the foundation for subsequent investigations into the existence and antigenic specificity of thymus-derived natural regulatory T cells (nTregs). These nTregs prevented the development of autoimmune thyroiditis, despite the ever-present genetic predisposition, autoantigen (thyroglobulin), and thyroglobulin-reactive T cells. Guided by the hypothalamus-pituitary-thyroid axis as a fixed set-point regulator in thyroid hormone metabolism, we used a murine model and compared at key junctures the capacity of circulating thyroglobulin level (raised by thyroid-stimulating hormone or exogenous thyroglobulin administration) to strengthen self-tolerance and resist autoimmune thyroiditis. The findings clearly demonstrated an essential role for raised circulating thyroglobulin levels in maintaining the dominance of nTreg function and inhibiting thyroid autoimmunity. Subsequent identification of thyroglobulin-specific nTregs as CD4+CD25+Foxp3+ in the early 2000s enabled the examination of probable mechanisms of nTreg function. We observed that whenever nTreg function was perturbed by immunotherapeutic measures, opportunistic autoimmune disorders invariably surfaced. This review highlights the step-wise progression of applying insights from endocrinologic and immunologic studies to advance our understanding of the clonal balance between natural regulatory and autoreactive T cells. Moreover, we focus on how tilting the balance in favor of maintaining peripheral tolerance could be achieved. Thus, murine autoimmune thyroiditis has served as a unique model capable of closely simulating natural physiologic conditions.
Keywords: natural regulatory T cells; experimental autoimmune thyroiditis; autoreactive T cells; circulating thyroglobulin; thyroid-stimulating hormone; thyrotropin-releasing hormone